Um ser (tão) de vozes: o estilo e o acabamento estético na poesia de Patativa do Assaré - Matias, Janaína Moreno (2012)
The present study aims at investigating the style of the Cearense 1poet Patativa do Assaré in his poetic discourse Cante lá que eu canto cá (2004). Such choice is due to the fact that Assaré‟s poetry is full of regional identities as well of different voices. In other words, our purpose is to analyze the way the author aesthetically expresses his own voice and the voice of others in his work. This study is based on a social and historical model of language, with language construed as a discourse practice with emphasis on the key concepts of style, voices, subject and dialogic relationships (BAKHTIN, 1992, 2003, 1995). Our documental research is situated within the area of Applied Linguistics and presents an interface with Literature. We start out with the premise that in this type of investigation knowledge is built from language. In this sense, we must consider the social relationships in which language is produced, as well as the world which (in) determines, interferes, represents, interpenetrates or else, reformulates language and the indisciplinary character of the research